دور استخدام نظم المعلومات التسويقيَّة في تحسين الميزة التنافسيَّة "دراسة ميدانيَّة على الشَّركات الصِّناعيَّة العاملة في السَّاحل السُّوري" - حسون عتاب; دبس يامن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
جاء هذا البحث للوقوف على مدى تأثير استخدام نظم المعلومات التسويقيَّة في تحسين الميزة التنافسيَّة بأبعادها الخمسة (الجودة، التَّكلفة، المرونة، السُّرعة والإبداع)، وذلك في عيِّنة من الشَّركات الصناعيَّة العاملة في السَّاحل السُّوري. قام الباحث بتوزيع (115) استبياناً على المديرين والعاملين والعملاء في الشَّركات محل الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (86) استبانة. قام الباحث بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّل الباحث إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لاستخدام نظم المعلومات التسويقيَّة على تحسين الأبعاد الخمسة للميزة التنافسيَّة في الشَّركات محل الدراسة. كما تقدَّم الباحث في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة تطبيق نظم المعلومات التسويقيَّة في الشَّركات محل الدراسة، والاهتمام بتدريب المديرين والعاملين ومتَّخذي القرارات فيها على استخدام هذه النظم وزيادة معارفهم بمجالات استخدام الحاسوب والبرامج ذات العلاقة، كما يجب على إدارة الشَّركات محل الدراسة: العمل على التَّحسين المستمر لنمط التِّقانة المستخدم والمرافق والتَّجهيزات والأدوات والمعدَّات التِّقنية والإداريَّة الخاصَّة بهذه الشَّركات، إشراك العاملين في تقييم فاعليَّة البرامج المستخدمة بشكلٍ مستمر، توفير البدائل المتعدِّدة عند اتِّخاذ القرارات الإداريَّة، المواكبة المستمرَّة للمستجدَّات التِّقنيَّة في مجال تطبيق واستخدام نظم المعلومات التسويقيَّة. This research was conducted to determine the effect of the use of marketing information systems on improving the five-dimensional competitive advantage (quality, cost, Flexibility, speed and creativity) in a sample of industrial companies operating in the Syrian coast. The researcher distributed (115) questionnaires to managers, employees and clients in the companies under study. The number of recovered and valid questionnaires which were discharged was (86). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the use of marketing information systems to improve the five dimensions of competitive advantage in the companies under study. The researcher also made a number of recommendations, including: The need to apply the marketing information systems in the companies under study, and the interest in training managers and employees and decision makers in the use of marketing information systems and increase their knowledge in the areas of computer use and related programs, and the management of the companies under study should: work on continuous improvement of the type of technology used, facilities, equipment, equipment and technical and administrative equipment of these companies, involve the employees in evaluating the effectiveness of the programs used continuously, providing multiple alternatives when making administrative decisions, keeping abreast of technical developments in the field of application. And the use of marketing information systems.